Computer experiments using a two-dimensional model of tooth support. - Halazonetis, D J (Am J Orthod Dentofacial Orthop, 1996)
The purpose of this investigation was to study the factors that may affect the position of the center of resistance and center of rotation. A two-dimensional computer model of the periodontal ligament was developed. The model permitted the simulation of an isotropic (responding in the same manner regardless of the direction of the applied force) and nonisotropic periodontal ligament and allowed changes in root shape and in position and direction of force application. The center of resistance was found to depend on the distribution of root surface area. For a model of the upper central incisor, it was located at 42% of the root length measured from the alveolar crest. The presence of anisotropy in the periodontal ligament significantly affected the position of the center of resistance, which was in this case also affected by the direction of the applied force. Forces passing through the center of resistance produced translation of the modeled tooth in a direction not necessarily the same as the direction of the applied force. Tipping forces produced much larger stresses than forces causing translation. Simulation of periodontal involvement resulting in loss of attachment increased the stresses exerted on the periodontal ligament. The model permitted easy assessment of various factors that may influence the position of the center of resistance of teeth and revealed a potentially large variability in the position of the center of resistance and center of rotation, caused by variation of the properties of the periodontal ligament.
Keywords: Alveolar Process; computer simulation; Humans; Incisor; Models, Biological; Periodontal Attachment Loss; Periodontal Ligament; rotation; Stress, Mechanical; Tooth Movement Techniques; Tooth Root